Pengaruh nomophobia terhadap academic failure pada mahasiswa - Dhika Pamutri Rahayu; Fathul Lubabin Nuqul; Husnul Khotimah (University of Merdeka Malang, 2020)
Every student has the hope of achieving maximum or satisfactory learning achievement in his studies. An initial survey conducted on a number of students at the psychology faculty of Unmer Malang found that students experienced symptoms that led to academic failure, where the symptoms were: often not focused or unable to concentrate during lectures, easily gave up when faced with difficulties, felt unable to do work. tasks well, decreased interest in learning, doubting their own abilities, learning is considered a burden and something boring. One way to overcome this problem, students make a diversion by playing smartphones. This has a negative impact on the decline in student achievement. The purpose of this study was to determine the effect of nomophobia on student academic failure. The research design uses a quantitative survey approach, with the data collection technique using random sampling. After going through the regression test, it was found that there was an influence of nomophobia on academic failure of 0.211 (21.1%) on academic failure, which means that the hypothesis in this study was accepted.